THE AUTHORITY OF THE BALI PROVINCIAL GOVERNMENT IN LAW ENFORCEMENT AGAINST FOREIGN TOURIST GUIDES WITHOUT LICENSES - Rama, I Wayan Agus; Astara, I Wayan Wesna; Sepud, I Made (jfpublisher, 2024)
Tourism in Indonesia is experiencing rapid development, bringing both positive and negative impacts. However, with the rapid growth of tourism in Bali, the problem of unlicensed tour guides, or illegal guides, has emerged, which is detrimental to the quality of service and image of tourism. This research aims to analyze the local government's supervisory function towards illegal tour guides and examine the enforcement of legal sanctions against foreign tour guides based on relevant regulations. The researchers intend to further explore legal issues related to the authority of the Bali Provincial Government in enforcing the law against foreign tours without a license, focusing on the synchronization of rules between national and regional regulations to create better legal certainty. The results of this research show that the local governments in the Balinese province have the authority to enforce the law, and the local authorities in the province have a responsibility to ensure the integrity of the tourism sector. The research results also show that there is a need to improve the capacity of law enforcers in order to ensure optimal law enforcement, protect the tourism industry, and support the sustainable development of Bali tourism.